Types of Self-Care Recommendations Given for Adults with Type 2 Diabetes Mellitus, Attending a Diabetic Clinic in a Selected Teaching Hospital, Sri Lanka - Saumika, M.A.R.; Amarasekara, A.A.T.D. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2021)
Type 2 Diabetes Mellitus (T2DM) is a worldwide health problem and a significant issue in Sri Lanka. Self-care recommendations on diabetes self-care activities for patients with T2DM are vital parts of the clinical management of diabetes. There is a paucity of data regarding the types of self-care recommendations given by healthcare professionals for patients with T2DM in Sri Lanka. A descriptive cross-sectional study was conducted among purposively selected adults with T2DM (n=300)to determine the types of self-care recommendations given by healthcare professionals. Data were analyzed using descriptive statistics. Ethical approval was granted from the Ethics Review Committees of the Faculty of Medical Sciences and the Sri Jayewardenepura General Hospital. Types of self-care recommendations were assessed by using a pre-tested diabetes self- care activities questionnaire, which includes recommendations regarding diet, physical activities (PA), self-monitoring of blood glucose (SMBG) and testing urine for sugar. Out of 300 participants, the majority (68.7%) were female. From the participants, more than half (52.7%) had good glycaemia control (FBS≤ 126 mg/dl). Most of the participants (99.3%) received at least a single recommendation regarding their diet. Less than half (39%) of the adults have received all the recommendations regarding their PA from the list. Majority of the adults (73.3%) have received recommendations to get exercise such as walking and jogging daily. Of the sample, 67% received a recommendation to use a glucometer to self-monitor their blood glucose levels. Self-care recommendations were not significantly associated with glycaemia control. The health professionals need to provide more health education for adults with T2DM to maintain their self-care activities regularly.
Keywords: Type 2 diabetes, Self-care, Recommendations, Sri Lanka